Factors Predicting IPO Performance : An Analysis - Singh, Amit Kumar; Kalra, Shivani; Jham, Juhi (Indian Journal of Research in Capital Markets, 2018)
IPO is one of the most crucial events in the life of a company. The performance of an IPO is reflected by the benefits investors reap from investing into it. One of the ways of measuring those benefits is through analyzing the dividends declared by the companies which opted for going public through an IPO issue. This study attempted to identify factors that can help predict long run performance of IPO. In this paper, initially, 75 companies were taken across various industrial sectors that brought up an Initial Public Offer in 2010. Since the paper studied the long run performance of IPOs via dividends, it was inevitable to screen out companies that never declared dividends till date. Another screening criterion was non availability of information with respect to market capitalization, grades assigned, and subscription status. Dividends declared by companies, which came out with an IPO in 2010, were analyzed. A waiting period of 3 years was allowed for the companies to emerge, grow, and start distributing dividends, and dividend yields of the companies were calculated from 2014-2015. Empirical evidences supported the hypothesis that the market capitalization ofÂ an issue and the grade assigned to it are the major factors contributing towards an IPO’s success and thus, help in decision making by investors.